Effects of different mydriatics on intraocular pressure, pupil diameter, and ruminal and intestinal motility in healthy sheep - Ribeiro, Alexandre P.; Crivelaro, Roberta M. [UNESP]; Teixeira, Pedro Paulo M. [UNESP]; Trujillo, Dunia Y. [UNESP]; Guimaraes, Patricia J. [UNESP]; Vicente, Wilter Ricardo R. [UNESP]; Martins, Bianca da C. [UNESP]; Laus, Jose Luiz [UNESP] (Wiley-Blackwell, 2014)
Objective To determine the effects of the administration of subconjunctival 1% atropine (SA), topical 1% atropine (A), 0.5% tropicamide (T), 1% homatropine (H), 10% phenylephrine (P), and 2% ibopamine (I) on intraocular pressure (IOP), pupil diameter (PD), ruminal motility (RM) and intestinal motility (IM) in sheep.Animal studied Ten spayed ewes of Santa Ines breed.Procedures Six experiments were performed separately at 1-week intervals. One eye was randomly selected and received one drop of A, T, H, P, I, or subconjunctival injection of atropine at 8 a. m. On the following days, IOP and PD were evaluated every 8 h until the pupil returned to its normal diameter. Ruminal motility and intestinal motility were evaluated only within the first 13 h.Results The IOP did not change significantly in the treated eyes compared with the control eyes and baseline at any time point (P > 0.05). A longer-lasting pupil dilation was observed after the administration of A (96 h), SA (79 h), H (24 h), and T (24 h). Within the first 30 min after treatment, RM and IM decreased, by 78% and 82% (H), 76% and 86% (SA), 46% and 58% (A), and 62% and 70% (T) (P < 0.001), respectively, with a tendency to return to baseline values following 13 h of drug administration. Both 10% phenylephrine and 2% ibopamine did not have any effect on the parameters evaluated (P > 0.05).Conclusions Topical and subconjunctival 1% atropine, 0.5% tropicamide, and 1% homatropine significantly reduced RM and IM, and induced pupil dilation but did not change IOP in eyes of healthy sheep. The sympathomimetics phenylephrine (10%) and ibopamine (2%) did not change the parameters evaluated.
Keywords: atropine; parasympatholytics; phenylephrine; sheep; sympathomimetics; tropicamide